2016
DOI: 10.1093/jme/tjw078
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Bats, Their Ectoparasites, and Associated Pathogens on Saint Kitts Island

Abstract: Ectoparasites of bats and bat-associated pathogens are poorly studied in the Lesser Antilles Islands. We report on an 11-mo field study on Saint Kitts Island of bat populations, their associated ectoparasites, and pathogens. We report on five ectoparasite species, including four Streblidae (Diptera) and a Spinturnicidae (Acari). Several genotypes of unnamed Bartonella were isolated from bats and ectoparasites. Microfilaria of an undetermined Litomosoides spp. were detected in blood from Artibeus jamaicensis Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 50 publications
1
37
0
2
Order By: Relevance
“…These findings support the phylogenetic studies that have identified shared bartonellae in both bats and their ectoparasites. 14,[32][33][34][35][36][37][38][39] The bat-associated Bartonella strains isolated in Mexico also clustered with those previously described in bats and ectoparasites from other countries in Latin America. However, this is the first identification of Bartonella species in B. plicata, recognizing another bat genus to be infected with bartonellae.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These findings support the phylogenetic studies that have identified shared bartonellae in both bats and their ectoparasites. 14,[32][33][34][35][36][37][38][39] The bat-associated Bartonella strains isolated in Mexico also clustered with those previously described in bats and ectoparasites from other countries in Latin America. However, this is the first identification of Bartonella species in B. plicata, recognizing another bat genus to be infected with bartonellae.…”
Section: Discussionsupporting
confidence: 64%
“…DNA, 24 and in Saint Kitts island. 39 In Puerto Rico, Bartonella isolates were obtained from blood specimens of 9/51 (18%) individuals from three species (A. jamaicensis, Brachyphylla cavernarum, and Monophyllus redmani). 25 Across studies, Bartonella prevalence was the highest in hematophagous bats (42%, 66/158), followed by phytophagous (22.9%, 84/367) and insectivorous bats (19.3%, 42/217).…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies of Bartonella spp. in bats from Algeria [17], Madagascar and the Union of Comoros [18], French Guiana [19], Saint Kitts [20], South Africa [21], the Republic of Georgia [22], China [23], France and Spain [24], the United States [25], Argentina [26], and Brazil [27] have only added to this substantial diversity. Despite apparent phylogenetic patterns linking bats and bat-associated bartonellae, there is evidence that spillover of bartonellae from bats into other mammals is possible, particularly to humans and dogs [22,2832].…”
Section: Introductionmentioning
confidence: 99%
“…DNA of Rickettsia spp. was also detected in the blood samples of bats from Swaziland, South Africa and Saint Kitts Island [15,16]. A recent study conducted in Europe showed that Rickettsia spp.…”
Section: Introductionmentioning
confidence: 90%